A study of the influence of coflow on flame dynamics in impinging jet diffusion flames. Issue 8 (3rd August 2021) - Li, Hongxu; Jiang, Jieyu; Sun, Meng; Yu, Yongzhe; Sui, Chunjie; Zhang, Bin
Abstract : Non-premixed impinging jet flames with different coflow conditions are performed using PIV technology combined with numerical simulation to investigate flame instability in the vicinity of wall. Results indicate that the increase of coflow velocity results in a more chaotic flow field and higher fuel efficiency, and the increase of coflow temperature leads to ignition advance and the increase of NO concentration. These can be attributed to the coupling effect of Kelvin-Helmholtz instability, convective instability and Rayleigh-Taylor instability. High coflow velocity is more likely to induce Kelvin-Helmholtz instability and convective instability, and the increase of coflow temperature enhances Rayleigh-Taylor instability and convective instability. Due to the impact effect in the vicinity of wall, the flame instability is more likely to be induced at high coflow velocity. Meanwhile, the increase of coflow temperature can inhibit flame wrinkles. The flame dynamics is affected by turbulent mixing, head-on collision, shear and convective behaviors in non-premixed flames.